The Effects of Single Deep Jump Training on Slopes on Selected Biomechanical Variables of the Triple Jump in Athletes Under 20 Years of Age - Kazem, Alaa; Hussein, Ehab (Journal of Physical Education, 2025)
The study aimed to investigate the effect of individual long jump slops and its effect on some biomechanical variables of U20 of triple jump. It is hypothesized that there is statistically significant difference between the results of the pre and posttests in the biomechanical variables of U20 of triple jumps. To achieve the aim of the study, one group pre-test post-test experimental design is used. A sample of (6) triple jump players under 20 years from the specialized schools of the Ministry of Youth and Sports, is non-randomly chosen during the academic year (2023-2024). The pilot study was carried out to on Tuesday and Wednesday (10/24/2023) at 4:00 p.m. at the Ministry of Youth and Sports stadiums on a group of (6) players who participated in the main study. A three-month training program was applied for 11 weeks, three training sessions per week. The training sessions were designed to gradually increase in intensity on a daily, weekly, and monthly basis, following a scientific and precise method regarding intensity and rest periods between repetitions and sets. This approach was tailored according to the specific goals of each training session and the biomechanical variables targeted for development in each session. It was concluded that the work of the angles of the lead leg during push-off for athletes in the triple jump who are under 20 years old is positively affected by individual long jump training.